If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = 18 + -1x Reorder the terms: 2 + 3x = 18 + -1x Solving 2 + 3x = 18 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + 3x + x = 18 + -1x + x Combine like terms: 3x + x = 4x 2 + 4x = 18 + -1x + x Combine like terms: -1x + x = 0 2 + 4x = 18 + 0 2 + 4x = 18 Add '-2' to each side of the equation. 2 + -2 + 4x = 18 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 18 + -2 4x = 18 + -2 Combine like terms: 18 + -2 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 5+1.5(2d-5.4)=0.5 | | 9-0.3= | | (6/11)=(1/4)+(7/11)x | | V=pi/3*r^2h | | }[%[[^+]babanababJzmzbnzm | | 2/3x=1/5x+7 | | 6x-5x=x+2 | | x-4/5=x+2/7 | | 12+x/4=5x-7/3+2 | | 20-100=20w-100 | | 5=x/9-12 | | .40x+.05(12-x)=.10(-15) | | 5x-7=20-8x | | -18=18r+5r | | 8a-4(-5a-2)=-2(4-7a) | | a-5/3-5(a-4)/8=2a+8/4 | | 1/2X+6=-13 | | 5-4(3x-9)= | | 2(x-3)+3(x+9)=-29 | | 7f-1=45 | | (y+5/3)-3=6 | | 5e-6-4=-3 | | x(2x-2)+x(3x-4)=(5x+6)(x-4) | | -126=14*k | | 6z+5(z-6)= | | (5e-6)-4=-3 | | 4x-1-4x+7= | | 4x+x=-27 | | 21=-7*n | | -13=-8b-5b | | -6x-50+12x=64 | | 4x-4=27 |